1981
DOI: 10.1136/pgmj.57.672.656
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pneumothorax complicating Legionnaires’ disease

Abstract: Summary Spontaneous pneumothorax is a known but rare complication of pneumonia in adults. A case is described of Legionnaires’ disease complicated by spontaneous hydropneumothorax. So far as is known such an association has not been reported previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In one case, pneumothorax developed after abscess formation in the right upper lobe [2]. In another case, the authors concluded that the infection resulted in pulmonary necrosis and bronchopleural fistula, leading to pneumothorax [3]. In our case, spontaneous pneumothorax developed early, and without evidence of intrapulmonary cavity.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…In one case, pneumothorax developed after abscess formation in the right upper lobe [2]. In another case, the authors concluded that the infection resulted in pulmonary necrosis and bronchopleural fistula, leading to pneumothorax [3]. In our case, spontaneous pneumothorax developed early, and without evidence of intrapulmonary cavity.…”
mentioning
confidence: 62%
“…This results in a pressure gradient between the alveoli and the lung interstitium, and ultimately alveolar rupture. A search of publications in English on PubMed identified four cases of Legionella pneumonia and spontaneous pneumothorax [2–5]. In one case, pneumothorax developed after abscess formation in the right upper lobe [2].…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14] Spontaneous pneumothorax is a rare presenting feature of Legionella CAP. 15,16 To the best of our knowledge, this is the first report of bilateral spontaneous pneumothorax as the presenting radiological manifestation of Legionella CAP.…”
Section: Legionella Community-acquired Pneumonia (Cap) Presenting Witmentioning
confidence: 74%